The primacy of emotional bonds and behavioral dynamics in sustaining Indonesian community livestock centers beyond economic rationality - Ferdi Fathurohman; Titik Ekowati; Siwi Gayatri; Retno Adiwinarti (Interaction, Community Engagement, and Social Environment, 2026)
Background: Grassroots agricultural institutions, such as Indonesia's Community Livestock Centers/Sentra Peternakan Rakyat (SPR), frequently experience systemic stagnation once state subsidies are withdrawn. Traditional extension models, which predominantly rely on top-down economic incentives, frequently fail to sustain long-term collective action. This study investigates the interplay of rational, emotional, and behavioral (REB) factors driving farmer participation while mapping actor-network constellations to identify specific governance bottlenecks during institutional decay. Methods: A mixed-methods sequential explanatory design was employed. First, quantitative survey data from 120 smallholder beef cattle farmers in Subang Regency were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Second, qualitative data from 15 key informants were evaluated through Actor-Network Theory (ANT) to analyze the sociology of translation. Findings: The structural model demonstrated exceptional explanatory power (R² = 0.915). Rational and Behavioral factors were significant, but emotional factor (trust and solidarity) emerged as the primary driver (β = 0.747, f² = 2.991). ANT analysis revealed that failure typically occurs during the “enrollment” phase, when top-down metrics clash with local psychosocial realities, leaving non-human artifacts (communal pens and biogas digesters) abandoned. Conclusion: Emotional factors have the strongest influence on SPR participation compared with the other factors, which highlights the importance of fostering social motivation within the community. Consequently, we recommend integrating 'Social Fabric Indicators' into regional agricultural extension policies to foster more resilient, community-based farming institutions. Novelty/Originality of this article: This study empirically challenges the classical homo economicus assumption by innovatively integrating the REB framework with ANT. The study robustly demonstrates the predominance of emotional capital over economic rationality for institutional sustainability.